Job recruitment analysis on Faculty of Information Technology and Quantitative Science (FITQS)'s graduates / Siti Uraidah Udin - Udin, Siti Uraidah (2004)
Nowadays, the lack of trained Information Technology experts and knowledge workers in supporting application diffusion in the public sector is a major challenge in the efforts to expand the use of Information of Communication Technology in the country. As working mechanism have received growing attention from entrepreneurs, executives, investors and industry, Faculty Of Information Technology And Quantitative Science graduates have progressively come to be considered a critical part for developing a successful graduates in getting a job. Based on an earlier policy-capturing study of the Big Five personality traits by J.M Digman and general mental ability, this research explores and analyzes the recruitment preference on Faculty of Information Technology and Quantitative Science's graduates across five important personal attributes, including not only personality but also practical skill dimensions. Among knowledge, skills, abilities, and personality, the personality of a candidate has a relatively greater impact on the hiring decision. The other attributes, in order of importance, include conscientiousness, communication skills, and openness to new experiences, friendliness, and agreeableness Skill has been defined as the application of prior knowledge and experience to successfully achieve a specific outcome. From the previous Big Five personality traits, the Job Recruitment Model was produce and skills and knowledge become part of them. This is because from the chisquare analysis and correlation analysis show that it is dependent to job recruitment and has significance towards job recruitment. The results of this study show that all this attributes are required in getting a job and the new model is develop.